Measuring the risk, efficiency, and effectiveness of banks in Malaysia using data envelopment analysis model / Nur Amira Syifa' Azli, Noor Asiah Ramli and Norbaizura Kamarudin - Azli, Nur Amira Syifa'; Ramli, Noor Asiah; Kamarudin, Norbaizura (Universiti Teknologi MARA, Selangor, 2022)
The banking system plays a significant role in every country by facilitating economic growth and affecting the money supply. However, the phenomenon of rapidly growing foreign banks in Malaysia has led to intense competition between domestic and foreign banks. This scenario has prodded bank managements to improve their performance so as to ensure their banks will remain strong and relevant. The main purpose of this study is to measure and analyze three indicators of profitability, namely the risk, efficiency, and effectiveness of banks in Malaysia from 2015 to 2019 using Data Envelopment Analysis (DEA) method. These three indicators have not been examined together in Malaysian studies that looked at the performance of banks in the country. The study utilized secondary data for eight domestic banks and eight foreign banks in Malaysia. Foreign banks were found to attain slightly higher scores than domestic banks for all the evaluated indicators encompassing risk, efficiency, and effectiveness. Concerning risk, the results can be interpreted as foreign banks were more efficient than domestic banks at managing risk. Overall, foreign banks performed marginally better than domestic banks based on the performance score results.